2006
DOI: 10.1111/j.1742-4658.2006.05245.x
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively active α subunits of Gq/11 and G12/13 families inhibit activation of the pro‐survival Akt signaling cascade

Abstract: Accumulating evidence indicates that G protein signaling plays an active role in the regulation of cell survival. Our previous study demonstrated the regulatory effects of Gi/o proteins in nerve growth factor‐induced activation of pro‐survival Akt kinase. In the present study we explored the role of various members of the Gs, Gq/11 and G12/13 subfamilies in the regulation of Akt in cultured mammalian cells. In human embryonic kidney 293 cells transiently expressing constitutively active mutants of Gα11, Gα14, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 56 publications
(74 reference statements)
0
20
0
Order By: Relevance
“…Interestingly, although this pathway seems to be activated by most G q PCRs (11), some reports showed that activation of certain G q proteins actually reduces AKT activation. These include a GnRH receptor that counteracts IGF-1 in ␣T3-1 cells (23), a m1 muscarinic receptor that counteracts insulin in HeLa cells (24), and constitutively active G q that counteracts EGF in HEK293 cells (25). However, the mechanism of G q PCRs effect on growth factor-induced AKT activation is not fully elucidated.…”
mentioning
confidence: 99%
“…Interestingly, although this pathway seems to be activated by most G q PCRs (11), some reports showed that activation of certain G q proteins actually reduces AKT activation. These include a GnRH receptor that counteracts IGF-1 in ␣T3-1 cells (23), a m1 muscarinic receptor that counteracts insulin in HeLa cells (24), and constitutively active G q that counteracts EGF in HEK293 cells (25). However, the mechanism of G q PCRs effect on growth factor-induced AKT activation is not fully elucidated.…”
mentioning
confidence: 99%
“…Likewise, luteinizing hormone-releasing hormone receptor strongly diminishes the anti-apoptotic effect of IGF-1 through inhibition of Akt activation. Our recent experimental results also demonstrated that other activated ␣ subunits of the G q family (G ␣ 11 , G ␣ 14 , and G ␣ 16 ) can attenuate basal and EGF-induced Akt activities and the phosphorylation of tuberin in a PLC ␤ -and Ca 2+ mobilization-independent manner [109] . In agreement, a number of recent studies have shown that the pro-apoptotic effect of G q/11 is neither dependent on PLC ␤ activity [110] nor on the elevation of intracellular calcium [111] .…”
Section: Mechanisms Of Tuberin Regulation By Gpcrsmentioning
confidence: 96%
“…Some of our current experimental data demonstrated that activated G 12 and G 13 are able to inhibit Akt and tuberin phosphorylation via RhoA [109] . Overexpression of the constitutively active G ␣ 12 and G ␣ 13 (G ␣ 12 QL and G ␣ 13 QL) is apparently sufficient to inhibit the EGF-induced Akt activation and tuberin phosphorylation in human embryonic kidney (HEK293) cells.…”
Section: Mechanisms Of Tuberin Regulation By Gpcrsmentioning
confidence: 97%
“…The gene GNAS1 encodes the ubiquitously expressed G(alpha)s (Gas) subunit of heterotrimeric G proteins. In vitro experiments suggest, that increased expression of Gas is associated with enhanced apoptosis and that the second messenger, cyclic AMP (cAMP), which functions downstream the G proteins, plays a major role in pro-apoptotic processes [5][6][7][8][9]. We have recently shown that genotypes of the common T393C single nucleotide polymorphism (SNP) of the GNAS1 gene are significantly associated with the clinical outcome of patients suffering from bladder cancer [10], colorectal cancer [11], clear cell renal cell carcinoma [12], and B-cell chronic lymphocytic leukaemia [13].…”
Section: Introductionmentioning
confidence: 99%